The vanadate-sensitive ATPase from plasma membrane of maize roots - Tatiana Pšenáková; Slavomira Kašiarová (Acta Societatis Botanicorum Poloniae, 2014)
Plasma membrane vesicles isolated from corn roots were shown to possess Mg2+- dependent and K+ - stimulated ATPase activity, which was inhibited by vanadate, insensitive to nitrate and molybdate, and very little sensitive to azide. The optimum of phosphohydrolase activity was at pH 6.5 and temperature optimum 40oC. ATP was the preferred substrate. The Plasma membrane ATPase was reconstituted into soybean phospholipid liposomes.